Development And Application Of Yielding Steel Plate Damper To Improve Seismic Performance Of Structures - Teruna, Daniel Rumbi (2017)
Passive damper has been widely used to improve seismic performance of structures by adding damping, and in some cases also adding stiffness. In the case of damping, the energy input is dissipated by various mechanisms. One of the common and inexpensive ways to absorb input energy induced by earthquake is through inelastic deformation of steel material. A desirable steel damper possesses three important characteristic, namely: to have stable and large energy dissipation capability, to have large initial stiffness, and to have a representative mathematical model. The drawback of the previous steel damper makes it important in finding new ways to developed steel damper that meets the criteria of a good steel damper. In this study, four specimens of steel plate damper with diamond hollow shape were developed and tested under cyclic increasing load. The results confirmed that the steel dampers with convex shape and straight shape at the side part exhibit good performance without any degradation in stiffness and strength. However, in term of energy dissipation capability and elastic stiffness, steel damper with convex shape possessed better performance compared to steel damper with the straight shape. In addition, all steel specimens possess a damping ratio > 40% at moderate displacement, while damping ratio of 50% is reached at large displacement for specimen with convex shape at side part. For engineering application, numerical modeling and analysis were also performed. It was found that the proposed mathematical model (Chaboche or modified Chaboche) and simplified models agreed well with the experimental results. Furthermore, to describe the effect of steel damper in enhancing the seismic performance of structure, a four story steel frame with and without steel damper were investigated under three selected ground motion records that matched the response spectra design of Indonesian code. The results showed that stiffness ratio (SR) was very important for steel frame structures equipped with steel damper to provide good performance under seismic excitation. The response parameters in term of story drift, base shear demands, input energy demand, and hysteretic energy demand are significantly influenced by stiffness ratio (SR). Finally, to quantify the seismic performance of the entire structures with different stiffness ratio, damage and inter-story drift index are determined and summarized . It was concluded that the use of steel damper with SR = 4.0 can reduce inter-story drift index from 2.33% to 0.89%, and damage index from 0.76 to 0.51.